MiR-940 Suppresses Tumor Cell Invasion and Migration via Regulation of CXCR2 in Hepatocellular Carcinoma. (11th October 2016) - Ding, Dong; Zhang, Yaodong; Yang, Renjie; Wang, Xing; Ji, Guwei; Huo, Liqun; Shao, Zicheng; Li, Xiangcheng
Abstract : Aim . To investigate the expression of miR-940 in the hepatocellular carcinoma (HCC) and its impact on function and biological mechanism in the HCC cells. Methods . Quantitative RT-PCR analysis was used to quantify miR-940 expression in 46 cases of tissues and cells. Transfection of HCC cell lines was performed by miR-940 mimics; the abilities of invasion and migration were assessed through Transwell array. Western blot represents the alteration in expression of CXCR2 by miR-940 mimics. Results . miR-940 expression was decreased significantly in the HCC tissues and the relevant cell lines. miR-940 upregulation suppressed the invasion and migration of HCC cells in vitro. Furthermore, the CXCR2 was downregulated to suppress invasion and migration after miR-940 mimics. Moreover, decreased miR-940 expression was negatively correlated with Edmondson grade (P = 0 . 008 ), tumor microsatellite or multiple tumors (P = 0.04 ), vascular invasion (P = 0.0 35 ), and recurrence and metastasis (P = 0.038 ). Kaplan-Meier analysis demonstrated that decreased miR-940 expression contributed to poor overall survival (P < 0.0 5 ). Conclusions . Our findings present that miR-940 acts as a pivotal adaptor of CXCR2 and its transcription downregulated CXCR2 expression to decrease HCC invasion and migration in vitro. Our study suggests that miR-940 may be a novel poor prognostic biomarker for HCC.